A population study of the association between sleep disturbance and suicidal behaviour in people with mental illness. (November 2016) - Stubbs, Brendon; Wu, Yu-Tzu; Prina, A. Matthew; Leng, Yue; Cosco, Theodore D.
Abstract: Limited representative research has considered the relationship between sleep disturbance and suicidal behaviour among people with mental illness. We investigated the relationship between sleep disturbance and suicidal behaviour across Part II interview of the National Comorbidity Survey Replication (NCSR). The associations between sleep disturbance and suicidal behaviour (thoughts, plans and attempts) were investigated using logistic and multinomial logistic regressions and stratified across six mental disorder groups (depression, anxiety, substance use disorders (SUD), eating disorders (ED), bipolar disorders (BD) and early life disorders). From 5701 participants (mean age 43.4 years 58% women), people with any mental disorder experiencing sleep disturbance were at increased odds of suicidal thoughts (odds ratio (OR): 2.5; 95% CI: 1.7, 3.6) and suicidal plans and attempts (OR: 5.7; 95% CI: 2.7, 11.9) adjusting for age, sex and income. People with BD (OR: 8.9; 95 CI: 2.1, 38.1), early life disorders (OR 6.98, 95% ci 2.48, 19.67), depression (OR 1.88, 95% CI 1.14, 3.11), anxiety (OR 1.90, 95% CI 1.28, 2.85) and SUD (2.60, 95% CI 1.23, 5.49) but not ED, were at increased odds of suicidal thoughts in the presence of sleep disturbance. Adjusting for anti-depressant intake attenuated the effect sizes by up to 20% but the associations remained significant. In conclusion, sleep disturbance is a potential risk factor for suicidal behaviours in people with mental illness. Monitoring and management of sleep disturbance in clinical practice might be an important strategy to mitigate suicidal behaviours in people with mental illness.